Erythropoietin and Red Progenitor Cell Function in Diabetic Patients with Kidney-Marrow Axis Disorder Under the Effect of Glucose Instability - AlFatlawi, Mustafa Hamza (Medical Science Journal for Advance Research, 2026)
Background: Chronic hyperglycemia alters metabolism beyond the blood vessels. It can also change the control of blood cells. It was essential to find out the relationship between glycemic instability based on HbA1c and renal medullary response. Objective: We closely monitored the secretion of erythropoietin (EPO) and the efficiency of erythroid activity in the bone marrow. Methods: In the period from February to October 2025, we conducted a prospective analytical study on 60 patients aged 45-85 years done at Al-Najaf Teaching Hospital. The study group included type 2 diabetes mellitus patients (n = 30) and healthy controls (n = 30). High-performance liquid chromatography (HPLC) was used to measure glycemic status. The measurement of serum erythropoietin levels was conducted through high-sensitivity enzyme-linked immunosorbent assay (ELISA); while hematological indices were analyzed through automated flow cytometry. Results: Diabetic patients showed significantly lower serum erythropoietin levels when compared with control subjects. The mean EPO level in diabetic patients was 7.4 ± 1.5 mIU/mL compared to a mean of 12.8 ± 2.1 mIU/mL in controls (P < 0.001). Despite the presence of clinical anemia, this reduction was noticed. A similar negative linear association was found between HbA1c and serum levels of EPO (r = 0.68). Moreover, the reticulocyte index was decreased suggesting impaired erythropoietin activity and the establishment of functional “EPO resistance” in the marrow. Chronic exposure of cells to high glucose levels seems to impair HIF-2α-regulated renal hypoxia-sensing. Conclusion: This interruption might lower the output of erythropoietin and weaken the response of erythroid progenitor cells. Based on the results, serum erythropoietin could be a useful biochemical marker for the detection of early or subclinical bone marrow dysfunction in elderly diabetic patients.